A general strategy for designing metal-free catalysts for highly-efficient nitric oxide reduction to ammonia. (15th February 2022) - Zhou, Qiang; Gong, Feng; Xie, Yunlong; Xia, Dawei; Hu, Zhigang; Wang, Sijun; Liu, Lishan; Xiao, Rui
Graphical abstract: Highlights: A strategy to design metal-free catalyst for nitric oxide reduction is developed. Molecular orbital theory and band theory are combined to study catalytic mechanism. A particular Ccenter -CN2 active site on hBN-graphene interface is discovered. The high-activity Ccenter -CN2 configuration is applicable to other 2D materials. Abstract: Electrochemical reduction reaction of nitric oxide (NORR) to ammonia has been considered as a promising alternative to capturing and utilizing NO emitted from thermal-power plants. Various metal-containing catalysts have been proved to possess efficient catalytic activities for NORR, yet the attempt on metal-free NORR catalysts is quite limited. Herein, by employing first-principle calculations, we propose a novel strategy of designing metal-free NORR catalyst by introducing Ccenter -CN2 configuration into hexagonal boron nitride-graphene heterostructures (hBN-graphene). The hBN-graphene heterostructures demonstrate excellent NORR activity, achieving a fairly low limiting potential of −0.22 V. The superior NORR activity is ascribed to the introduced unique configuration at the modified hBN-graphene interface. Moreover, the hBN-graphene heterostructures can efficiently suppress hydrogen evolution—the main competitive reaction. The ab-initio molecular dynamic simulations indicate that hBN-graphene heterostructures can retain considerable thermal stability. Our work opens an avenue to design metal-free catalysts for NORR by modulating the interface in two-dimensional heterostructures.